Consideraciones sobre el papel y la importancia de la familia extensa en la organización social de Egipto en el III milenio antes de Cristo - (:unkn) unknown (Universidad de Buenos Aires. Facultad de Filosofía y Letras. Instituto de Historia Antigua Oriental "Dr. Abraham Rosenvasser", 2006)
Although the Ancient Egyptian society has been traditionally considered as composed of nuclear families, recent developments in archaeological as well as textual research reveal that stem families were firmly embodied in the social organization of pharaonic Egypt in the third millennium BC. Official sources, such as the architectural, iconographic and epigraphic program present in Egyptian monuments, and the State census of the inhabitants of the Nile Valley, show a biased view of the Egyptian society which is challenged by the private documents concerning family affairs. Critical evidence for the importance of stem families comes from the recurrent periods of State crisis, when new social values and terms are expressed in the material record, and which are often very different from those prevailing in the official sources.
Estudios sobre parentesco y Estado en el Antiguo Egipto
82 ref.
Keywords: Historia egipcia; Historia antigua; historia social; antropología; parentesco; familia; nobleza; matrimonio; organización colectiva; Estado; Egipto